Growth of Aureobasidium pullulans on straw hydrolysate. - Han, Y W (1976)
Growth characteristics and cell properties of Aureobasidium (Pullularia) pullulans were studied. The organism grew well on an acid hydrolysate of ryegrass straw over a wide range of pH and temperature. The optimum temperature and pH for the growth of the organism were 32 degrees C and 5.5, respectively. A cell yield of 1.5 g/liter of straw hydrolysate was obtained. The dried cell mass contained 42.6% crude protein, 0.4% crude fat, and 6.4% nucleic acids. The essential amino acid profile of the microbial protein was comparable to that of Candida utilis. A rat feeding study indicated that the A. pullulans cells were not toxic and that the feed intake, weight gain, and protein efficiency ratio values were superior to those obtained with C. utilis. Once the question of mathogenicity is resolved, A. pullulans could be useful for production of single-cell protein from cellulosic wastes.